Perceptions of experiences with interprofessional collaboration in public health nursing: a qualitative analysis - Dahl, Berit Misund; Crawford, Paul (Taylor & Francis, 2017)
In public health nursing interprofessional collaboration has become a goal, however, there is little clarity on the distribution of responsibility or approach to cooperation between the professional groups. The aim of the study was to explore public health nurses’ perceptions of their experiences related to interprofessional collaboration. A qualitative content analysis was carried out. An interview study with a purposeful sample of 23 Norwegian public health nurses (PHNs) was conducted. Data were analyzed using semi-structured interviews to identify categories and themes of PHNs’ working lives. The data were classified into three major themes: institutionality: the institutional understanding of the professional roles; competence: clarifying jurisdictional borders, and recognition: professionals` recognition of different roles. There needs to be a robust strategy in collaborative working that involves public health nurses among other professionals to avoid role overlap, interpersonal and interprofessional conflict and reduce the damaging threat or stress that comes with informal or ad hoc rules of engagement and status claiming by one profession over another.